The Harvard Department of Economics from the Beginning to World War II - Mason, Edward S.; Lamont, Thomas S. (Quarterly Journal of Economics, 1982)
Journal Article The Harvard Department of Economics from the Beginning to World War II Get access Edward S. Mason Edward S. Mason Thomas S. Lamont University Professor, Emeritus Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 97, Issue 3, August 1982, Pages 383–433, https://doi.org/10.2307/1885870 Published: 01 August 1982